IRON STATUS IN ANEMIA OF CHRONIC KIDNEY DISEASE (CKD) STAGE-V AND ITS IMPROVEMENT WITH INTRAVENOUS IRON SUPPLEMENTATION - RATNA PALIT,; DIVYA AGRAWAL,; KARMAJEET RATH,; SANJAY KUMAR,; RABINDRANATH SAHOO,; JYOTSNA PATNAIK, (International Journal of Pharma and Bio Sciences, 2014)
89 cases of chronic renal failure CKD stage-V were materials for the study. All the cases (100%) had severe degree of anemia. 41 cases had iron deficiency with a mean TSAT 10.71 ± 3.10% and serum iron 20.95 ± 4.78µg/dl which was significantly lower than the control group and from patients who did not have iron deficiency. However serum ferritin was higher than the control which was due to the reason that all these cases had severe degree of inflammation (CRP +ve) and serum ferritin is known to be an acute phage reactant. After intravenous iron sucrose administration for 4 weeks the serum iron and TSAT increased to 89.40 ± 3.56 µg/dl and 24.11 ± 1.78 % respectively which were statistically significant p<0.01. But the hemoglobin rise was from 6.80 ± 0.150 to 7.80 ± 0.125gm%. The increase was not statistically significant. This indicates that other factors like erythropoietin deficiency is the main cause of anemia.